ABILITY OF BEEF BREED HEIFERS TO REPRODUCE DEPENDING ON THE LEVEL OF FEEDING - Гончарова, І. І. (Scientific Progress & Innovations, 2015)
There are some results of live weight and reproductive ability of Znamyanka interbreeding type of heifers of Polissian meat breeds with different levels of feeding. Optimal live weight and age of productive pairing heifers are established. Thus, intensive growth of heifers provides daily gain of 700-800 g and live weight of 385 kg at 15–16 month-old heifers. It is shown experimentally that intensively reared animals consumed less feed daily during the whole growing period, it was marked as the best reproductive ability, their age of productive pairing was 146 days less than in the control group of their yearlings. Indicators of their fertility were 6 % higher. These heifers were 4-5 months younger during the period of productive pairing, that indicates the higher precocity of intensively reared heifers.